Kachkaniraqmi: theparitarian andean social thought in the face of individualistic western thought (Revista revoluciones, 2020)
The andean Qapaq thought has been transmitted from generation to generation in the ayllus, where it maintains modes of thinking, own lifestyles, clearly differentiated from western and eurocentrist individualistic models of life. The objective of the study was to analyze the terms of andean Qapaq thinking and to differentiate western approaches. Under the qualitative methodology, the descriptions were traced bibliographically and the authors were interpreted in reference to the phenomenon of indigenous claim. It was evidenced that in the ayllus or native peasant communities such as Sucuca Urinsaya and the Sucuca Anansaya community, the practice of the andean principles of the Allin Yachay or Wali Yatiña, meaning to know well, is still in force. There is also the principle of the Allin Munay or Wali Munaña translated as wanting well and finally there is the Allin Ruray or Wali Luraña translated as doing well to achieve the Sumaq Kawsay. Therefore, these manifestations in the different daily work and activities of the communeros qhari-warmi or chacha-warmi, which means male and female, support the common philosophy of the true inhabitants of the invisibilized peoples of the Tahuantinsuyano Peru.
Keywords: Andean philosophy; decolonization; good living; periphery; eurocentrism